Рассказы и сказки - Бианки Виталий Валентинович (Школьная библиотека, 2018)
Экземпляры: ф.19 (2019) / Инвентарный номер: 55654 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Б 59 / ГРНТИ: 17.82.93 / ББК: 84(2=411.2)6